2021
DOI: 10.5194/soil-7-767-2021
|View full text |Cite
|
Sign up to set email alerts
|

Assessing soil and land health across two landscapes in eastern Rwanda to inform restoration activities

Abstract: Abstract. Land degradation negatively impacts water, food, and nutrition security and is leading to increased competition for resources. While landscape restoration has the potential to restore ecosystem function, understanding the drivers of degradation is critical for prioritizing and tracking interventions. We sampled 300–1000 m2 plots using the Land Degradation Surveillance Framework across Nyagatare and Kayonza districts in Rwanda to assess key soil and land health indicators, including soil organic carbo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 61 publications
1
5
1
Order By: Relevance
“…By contrast, fine-textured soils without aggregation have smaller pores which can, in cases such as vertisols, be further reduced during rainfall as a result of clay particles swelling, thereby inhibiting infiltration further (Medinski et al, 2009). We did not find a significant effect of soil pH on K fs (Table 2), although high pH has been associated with low infiltrability (Mills et al, 2006;Medinski et al, 2010;Winowiecki et al, 2021), an effect which may be ascribed to an increase in clay dispersibility at higher pH values (Chorom et al, 1994). The range of pH in our study may have been too limited to find a relationship between K fs and pH.…”
Section: Soil Propertiescontrasting
confidence: 55%
“…By contrast, fine-textured soils without aggregation have smaller pores which can, in cases such as vertisols, be further reduced during rainfall as a result of clay particles swelling, thereby inhibiting infiltration further (Medinski et al, 2009). We did not find a significant effect of soil pH on K fs (Table 2), although high pH has been associated with low infiltrability (Mills et al, 2006;Medinski et al, 2010;Winowiecki et al, 2021), an effect which may be ascribed to an increase in clay dispersibility at higher pH values (Chorom et al, 1994). The range of pH in our study may have been too limited to find a relationship between K fs and pH.…”
Section: Soil Propertiescontrasting
confidence: 55%
“…The field-saturated conductivity was also greater for G. sepium vegetated contour compared to A. colei, which did not differ from A. gayanus. Litter, the major source of soil carbon, may have contributed to such difference as related by Bargués-Tobella et al (2024) and Winowiecki et al (2021) who found that soil organic carbon positively influenced Kfs. G. sepium is recognized for its positive role in improving land fertility through the production of nitrogen-rich leafy biomass and the ability of its root system to produce nodules (Kwesiga et al, 2003;Rosenstock et al, 2014;Tangata & Alavalapati, 2003;Wambugu et al, 2011).…”
Section: Discussionmentioning
confidence: 88%
“…(2024) and Winowiecki et al. (2021) who found that soil organic carbon positively influenced Kfs. G. sepium is recognized for its positive role in improving land fertility through the production of nitrogen‐rich leafy biomass and the ability of its root system to produce nodules (Kwesiga et al., 2003; Rosenstock et al., 2014; Tangata & Alavalapati, 2003; Wambugu et al., 2011).…”
Section: Discussionmentioning
confidence: 95%
“…In general, the health evaluation index of cultivated land systems should consider both macro-level management control and micro-level implementation feasibility due to the inherent characteristics of heterogeneity and diversity of cultivated land systems, the complexity and availability of multi-source data, and the varying objectives and needs of stakeholders at different levels. Future research should focus on the effects of climate change, annual accumulated temperature, annual precipitation index, ecosystem services, and other factors on the health of cultivated land systems on a macro scale [ 78 , 79 , 80 ] and on the effects of heavy metal pollution, soil organic carbon, soil erosion, soil organic matter, soil pH, soil nutrient elements (nitrogen, phosphorus, and potassium), soil texture, effective soil depth, and soil microorganisms on the health of cultivated land systems on a micro scale [ 17 , 81 , 82 ]. In addition, although the grid scale of 5 km × 5 km is utilized as the evaluation unit in this research, the scale effect of agricultural system health assessment must be studied further, with a focus on the impact of grid size on farming system health evaluation results and its spatial-temporal pattern.…”
Section: Discussionmentioning
confidence: 99%
“…The advancement of agricultural intensification, irrational fertilization, farming, grazing, crop types, and crop rotation plans will have a significant impact on the health of the cultivated land system [ 16 ], and environmental issues such as soil erosion, pollution, and biodiversity loss will become more prevalent. Agriculture has become the leading cause of environmental degradation on a global scale [ 17 , 18 ]. People have started to become more aware of the intimate connection that exists between healthy land and healthy people as a result of the complete promotion of an all-encompassing preservation strategy on the quantity, quality, and ecology of cultivated land [ 19 ].…”
Section: Introductionmentioning
confidence: 99%